Analisis Isi Video YouTube® Berbahasa Indonesia yang Berhubungan dengan Depresi - Dicky Sanjaya; Widodo Sarjana; Alifiati Fitrikasari; Sri Woroasih (Majalah Kedokteran Indonesia, 2024)
Introduction: Nowadays, mental health literacy through internet videos, such as YouTube®, plays an important role for individuals experiencing depression. However, the majority of YouTube® videos related to depression are generally in English. This study aims to provide an overview of Indonesian-language YouTube® videos related to depression.Methods: The keyword “depression” is entered into the YouTube® search engine, and based on the highest number of views, the top 100 videos are selected for analysis regarding the characteristics of the videos and various information related to depression. This includes causes of depression, symptoms of depression, prevention/therapy of depression, recovery from depression, and sources of information about depression. Each characteristic will be compared based on the number of views, likes or dislikes, and number of comments. Results: Only 10% of Indonesian-language videos with the keyword “depression” are uploaded by professional channels, and 6.57% of the videos are sourced from professionals. Most videos do not provide information about prevention or therapy (57%) and the recovery from depression (78%). The majority of the videos mention that depression is caused by life stress (49%) with symptoms of suicidal thoughts (39%) and sadness (25%). However, only 16% of the videos state that depression can be treated or prevented with professional consultation. Conclusion: Depression literacy through Indonesian-language YouTube® videos is still lacking. There is a need for YouTube® videos that provide information about depression, come from professional sources, and include encouragement to seek professional help.